Construction of Clean Water Supply and Ablution Facilities at Al-Ikhlas Mosque - Muvi Yandra; Totoh Andayono; Yuwalitas Gusmareta; Henny Yustisia (Universitas Negeri Padang, 2025)
Padang Baru Jorong in Nagari Ganggo Hilia, Bonjol District, Pasaman Regency, is a rural settlement of approximately 30 households that is not served by a municipal water pipeline. Al-Ikhlas Mosque had relied on a shallow dug well with visually poor water quality, and the congregation had to draw water manually with a bucket because no permanent ablution facility was available. This community partnership activity aimed to provide a functional water-supply system and construct an accessible ablution facility for the mosque congregation and nearby residents. The program was implemented through field observation, coordination with local authorities and mosque managers, technical design and budgeting, procurement of materials, and 32 hours of construction work involving lecturers, students, and community members. The completed works included a water pump, a 500 L storage tank supported by a 2.5 m steel tower, PVC distribution pipes, a roofed ablution structure, and water faucets. The system conveyed water from the well to the storage tank and distributed it by gravity to the ablution points. The activity reduced the need for elderly congregants to lift water manually and improved the availability and convenience of water for worship. The project shows that a simple, community-based water installation can address basic service limitations in an unserved rural mosque